Trends of prostate cancer incidence and mortality in Shanghai, China from 1973 to 2009. Issue 14 (17th July 2015) - Qi, Di; Wu, Chunxiao; Liu, Fang; Gu, Kai; Shi, Zhuqing; Lin, Xiaoling; Tao, Sha; Xu, Wanghong; Brendler, Charles B.; Zheng, Ying; Xu, Jianfeng
<x xml:space="preserve">Abstract</x> Background The incidence and mortality of prostate cancer (PCa) were historically low in China but have increased considerably in recent years. This study aimed to describe the detailed trend of PCa incidence and mortality in Shanghai, China. Material and methods Incidence and mortality data of PCa in urban Shanghai during 1973 and 2009 were collected by the Shanghai Municipal Center for Disease Control and Prevention. Age standardized rates (ASR) of incidence and mortality were calculated based on the 1966 world standard population. Join point regression analysis was used to describe the trends and to identify specific time points when significant changes in incidence and mortality occurred. Results The PCa incidence in Shanghai increased ∼sixfold from an ASR of 2.13/100, 000 in 1973 to 12.96/100, 000 in 2009, and its rank ascended from the 17th to the 4th most common cancer during the period. The PCa mortality in Shanghai increased threefold from an ASR of 1.61/100, 000 in 1973 to 4.97/100, 000 in 2009, and its rank ascended from the 17th to the 6th most deadly cancer during this period. More specifically, the ASR of incidence increased slightly before 1991, sharply during1991–2004, and slightly after 2004, with annual percent changes (APC) of 2.2% (95% confidence interval: 0.3%−4.3%), 13.2% (11.4%−15.0%), and 3.2% (−0.3%−6.8%), respectively. The mortality trend was stable before 1985 and increased slowly but steadily after 1985, with APC of −0.6% (−4.4%−3.3%) and 5.3% (4.7%−6.0%), respectively. The increasing incidence and mortality rates were primarily observed in men ≥ 70 years. Conclusion The incidence and mortality of PCa have increased significantly in Shanghai, China over the past four decades. Prostate 75:1662–1668, 2015. © 2015 Wiley Periodicals, Inc.